EFFECTS OS PROBLEM -BASED LEARNING ON STUDENTS’ CRITICAL THINKING AND SELF DIRECTED LEARNING SKILLS - Ergasheva Mohidil (Journal of new century innovations, 2024)
Annotation: This theoretical article explores the influence of problem-based learning (PBL) on students' development of critical thinking and self-directed skills. By analyzing the theoretical underpinnings of PBL and its implications for student learning outcomes, this paper aims to provide insights into how PBL can enhance critical thinking abilities and foster self-directed learning behaviors among students. Drawing on existing research and educational frameworks, the article offers guidance for educators seeking to leverage PBL to promote higher-order thinking and student autonomy in educational settings.